Tool4S: A GUI-based python software tool for seismic station site selection data processing and analysis - Ding, Cheng; Jiao, Chengli; Zheng, Shuang; Zhao, Zhiyuan; Feng, Xiangdong (SoftwareX, 2025)
•Tool4S is a standalone application which can be used directly without installing other environments or packages, just like a standard Windows application.•Tool4S is extensible, supporting new data formats via a plugin system.•Tool4S provides PSD testing functionality to evaluate parameters before batch PSD calculations. Data quality is the foundation of further research. It’s essential to find a seismic station whose data could be collected without being significantly affected by surrounding noise sources. To meet this end, Tool4S, an open-source Python-based tool, has been developed for seismic station site selection data processing and analysis. Tool4S is user-friendly with a Graphical User Interface (GUI). It can be easily distributed to other computers as a stand-alone application after being packaged. It provides functions for handling raw seismic data files, including a plugin-based data reader functionality compatible with various seismic instrument formats. With interactive dialogs and widgets, users can configure customized parameters and process data from multiple sites with a single click. A key feature is its interactive interface for testing Power Spectral Density (PSD) parameters before batch calculations. Users can directly observe the effects of different parameters and save the optimal parameters using the configuration function. Tool4S also provides PSD and Probability Density Function (PDF) analysis functions, enabling users to evaluate site data quality and analyze background noise characteristics, which is essential for seismic station site selection and further analysis. Tool4S provides a streamlined workflow during site selection and has the potential to be a handy and practical tool for seismic data-related research.